Copper enhances tetracycline resistance via the efflux transporter CrdAB-CzcBA in Helicobacter pylori - Gao, Fanglin; Xiang, Wanquan; Zhang, Xiaoyan; Huang, Xiaoxing; She, Feifei; Wen, Yancheng (Frontiers in Medicine, 2025)
Helicobacter pylori infection is a significant risk factor for various gastrointestinal diseases, while the standard triple therapy for its eradication is increasingly compromised by antibiotic resistance. This study investigates the role of the CrdAB-CzcBA efflux pump and its regulation by copper in tetracycline resistance in H. pylori. Using minimum inhibitory concentration (MIC) determination and growth curve analysis, we found that the deletion of crdA or czcA significantly reduced tetracycline resistance, while overexpression of CrdAB-CzcBA under the urease promoter enhanced bacterial resistance by reducing intracellular tetracycline accumulation. Ethidium bromide and tetracycline accumulation assays confirmed that CrdAB-CzcBA mediates active efflux of tetracycline, contributing to reduced intracellular drug levels. Furthermore, copper supplementation upregulated the expression of CrdAB-CzcBA via the CrdRS two-component system, thereby promoting bacterial growth under tetracycline stress. Notably, copper-induced resistance was abrogated in ΔcrdR mutants, demonstrating the dependence of this mechanism on CrdRS. These findings highlight CrdAB-CzcBA as a critical efflux system in tetracycline resistance and emphasize the role of environmental factors, such as copper, in modulating bacterial antibiotic resistance, underscoring the need for strategies that account for metal ion influences in managing H. pylori infections.